Body roundness index and the risk of hypertension: a prospective cohort study in Southwest China - Qingqing Zhan; Qinyu An; Fuyan Zhang; Tianlin Zhang; Tao Liu; Yiying Wang (BMC, 2024)
Abstract Background Body roundness index (BRI) is an anthropometric measure related to obesity, combining waist circumference (WC) and height to more accurately reflect body fat. This study aims to investigate the relationship between BRI and the risk of hypertension using data from a prospective cohort study in Southwest China. Methods Data for the study were derived from Guizhou Population Health Cohort Study (GPHCS), established in 2010. A total of 9,280 participants (aged 18 to 95 years, mean 41.53 ± 14.15 years) from 48 townships across 12 districts/counties were surveyed at baseline through multistage stratified random cluster sampling. Cox proportional risk models were employed to analyze the association between BRI and the risk of hypertension, estimating hazard ratios (HRs) and 95% confidence intervals (CIs) after adjusting for confounding factors. The relationship between BRI and the onset time of hypertension was analyzed using the time failure acceleration model. Results Over a median follow-up period of 6.64 years, 1,157 participants were diagnosed with hypertension. After adjusting for confounding variables, each unit increase in BRI was associated with a 17% increase in hypertension risk (HR = 1.17, 95% CI: 1.11, 1.24, P for trend < 0.001). Compared to participants in the first quartile (Q1) of BRI, the risk of hypertension for those in the third quartile (Q3) and fourth quartile (Q4) was 1.31 (95% CI: 1.10, 1.56) and 1.53 (95% CI: 1.28, 1.84), respectively. Each unit increase in BRI advanced the onset of hypertension by 0.26 years (95% CI: 0.16, 0.35). Conclusion This study indicates that BRI has a positive association with hypertension and can accelerate the onset of hypertension in the Chinese population. It is suggested that reducing BRI by controlling abdominal fat may be one of the effective measure to prevent hypertension.